KAJIAN LITERATUR TENTANG SKALABILITAS DAN KINERJA PROTOKOL VXLAN-EVPN PADA ARSITEKTUR JARINGAN DATA CENTER - Ferdiansyah Ferdiansyah; Yulindon Yulindon (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2026)
The advancement of cloud computing, virtualization, and distributed applications has increased the demand for scalable and high-performance data center network architectures. Traditional networks based on Virtual Local Area Network (VLAN) have limitations in terms of segmentation and efficiency, making them less suitable for modern data center environments. Therefore, Virtual eXtensible Local Area Network (VXLAN) combined with Ethernet Virtual Private Network (EVPN) as the control plane has emerged as a widely adopted solution. This study aims to analyze the scalability and performance of the VXLAN-EVPN protocol in data center network architectures. The method used is a Systematic Literature Review (SLR) by collecting and analyzing scientific articles from various databases within the period of 2021–2025. The results indicate that VXLAN improves network scalability through the use of Virtual Network Identifier (VNI), while EVPN enhances the efficiency of network information distribution using a Border Gateway Protocol (BGP)-based mechanism. In addition, the implementation of VXLAN-EVPN in a spine–leaf architecture is able to maintain network performance in terms of latency and throughput. Therefore, VXLAN-EVPN is an effective solution for supporting scalable and efficient modern data center networks.